Application of Chained Verse Learning in Improving Ability to Memorize Al-Quran Verses - Anita Suryani; Rahmat Mulyono (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
As a basic education institution that implements the 2013 curriculum, SD N Karangtengah IV has an obligation to equip students with basic competencies in demonstrating memorizing letters in the Koran. The learning process carried out is directed to the success of students in understanding the subject matter. Student success in learning is marked by students being able to achieve KKM scores. Based on student learning outcomes for the ability to memorize on basic competencies, it shows that the memorization of the Al Quran Surah At Tiin only reaches an average. The number of students who were able to achieve a score equal to or exceeding the KKM that had been set was only 33% of the fifth grade students at SD N Karangtengah IV.  The application of the Chained Verse Learning Model (ABer) aims to improve the results of memorizing QS. At Tiin For Class V Students of SD N Karangtengah IV Gunungkidul Regency for the 2022/2023 Academic Year. This research was conducted at SD N Karangtengah IV with the subject of fifth grade students totaling 25 students. Data collection was carried out using observation techniques, document analysis, and tests. Data analysis used is descriptive analysis technique. The research was carried out in two cycles which included the planning, implementation, observation and interpretation stages, as well as the analysis and reflection stages. Based on the results of the study it can be concluded that there is an increase in the success of learning to memorize QS. At Tiin which was marked by an increase in the average score of 64 in the pre-cycle, in the first cycle it increased to 74 and in the second cycle to 83.